Efektivitas Psikoedukasi Wawasan Kebangsaan untuk Menurunkan Kecenderungan Radikalisme pada Mahasiswa - Eko April Ariyanto; Sayidah Aulia Ul Haque; Achmad Rizal Syafii (Philanthropy: Journal of Psychology, 2019)
This research is motivated by the growing understanding of radicalism in Indonesia, including among the young generation of Indonesia. The younger generation should be the hope of the nation to continue the struggle of the predecessors to advance Indonesia, but if the young generation has been exposed to radicalism, it is necessary to provide an intervention in this case in the form of psychoeducation. The purpose of this study was to determine the effect of "Nationality Insight" psychoeducation on the emergence of radicalism in students. This study uses a comparative quantitative approach with data collection using non-probability sampling techniques in the population at the University August 17, 1945. The results of the Paired Sample T Test obtained significance of 0.104> 0.05. The results of the Paired Sample T Test on the pre-test and post-test scales in the group treated in the form of Nationality Psychoeducation obtained a significance of 0,000 <0.05. The results of this study prove that the "National Insight" psychoeducation method is effective in reducing the attitude of radicalism to students.Keywords: National Insight, Radicalism, StudentsDaftar PustakaAly, Abdul, (2011). Pendidikan Islam Multikultural di Pesantren, Yogyakarta: PustakaPelajar.  Ancok, D. (2008). Ketidakadilan Sebagai Sumber Radikalisme dalam Agama: Suatu Analisis Berbasis Teori Keadilan dalam Pendekatan Psikologi. Jurnal Psikologi Indonesia 2008, No. 1, 1-8, ISSN. 0853-3098  Cross, R. (2013). Radicalism. dalam Snow, D., della Porta, D., Klandermans, B., dan McAdam, D. (eds.). The Wiley-Blackwell Encyclopedia of Social and Political Movements. doi: 10.1002/9781405198431.wbespm175  Departemen Pendidikan Nasional. (2002). Kamus Besar Bahasa Indonesia ed. III. Jakarta: Balai Pustaka  Diktis.kemenag.go.id/NEW/index.php?berita=detil&jenis=news&jd=162.#.XeyoM25uLtQ. Diakses pada tanggal 8 Desember 2019  Endang Turmudi,   Riza  Sihbudi.   (2005). Islam  dan   Radikalisme  di  Indonesia.   Jakarta: Lembaga Ilmu Pengetahuan Indonesia  Hasyim, M., dkk (2015). Diskursus Deradikalisasi Agama: Pola Resistensi Pesantren terhadap Gerakan Radikal. Jurnal Penelitian Sosial Keagamaan. UIN Wali Songo  Kolb, D. (1984). Experiential Learning: Experience as the Source of Learning andDevelopment.  Latipun. 2004. Psikologi Eksperimen. Malang: UMM Press  McCauley, C. dan Moskalenko, S. (2008). Mechanisms of Political Radicalization: Pathways Toward Terrorism. Terrorism and Political Violence, 20:3, 415-433. doi:10.1080/09546550802073367  Moskalenko,  S.  dan  McCauley,  C.  (2009).  Measuring  Political  Mobilization:  TheDistinction Between Activism and Radicalism. Terrorism and Political Violence. 21:2,239-260. doi:10.1080/09546550902765508  Nelson-Jones, R. (1982). The theory and practice of counselling psychology. London: Holt, Rinehart and Winston  Rahimullah,    Riyad    Hosain,    Setephen    Larmar,    and    Mohamad    Abdalla.    (2013). € Radicalization and Terrorism: Research within the Australian Context. €ŸInternationalJournal of Criminologyand Sociology. Vol. 2. Hlm 180-185.  Saifuddin, (2011). Radikalisme Islam di Kalangan Mahasiswa. Jurnal Studi Keislaman Vol.   XI   No.   1   (Juni,   2011),   28.  Salehuddin, A. (2012). Understanding Religious Violence In Indonesia: Theological, Structural and Cultural Analyses. Journal of Indonesian Islam. UIN Sunan Ampel Surabaya  Seniati dkk. (2005). Psikologi Eksperimen. Jakarta: PT. Indeks  Taylor, D. C. M., & Hamdy, H. (2013). Adult learning theories: Implications forlearning and teaching in medical education: AMEE Guide No. 83. MedicalTeacher, 35(11), e1561 e1572. https://doi.org/10.3109/0142159X.2013.82815